Ahmadi & Co. Syirkah Pattern on Midai Island: A Study of Islamic Economic Concept Based on Partnership And Profit Sharing - Kartubi Kartubi; Rahimin Rahimin; Dahlia Dahlia (Journal Markcount Finance, 2025)
This study aims to examine the syirkah pattern implemented by the Ahmadi & Co Union on Midai Island from its founding in 1906 until its decline at the end of the 20th century. The partnership pattern between capital owners and plantation managers reflects the implementation of syirkah al-muzara'ah and syirkah al-musaqah in classical Islamic economic practices. This study uses a descriptive qualitative approach with a case study method. The results show that the Ahmadi & Co Union successfully implemented an Islamic economic system based on profit sharing and kinship, but experienced decline due to weak legal documentation and internal conflicts between heir families. This study contributes to the study of cooperative revitalization based on sharia values in Indonesia's border regions.